Hydrogen Evolution Reaction by Atomic Layer‐Deposited MoNx on Porous Carbon Substrates: The Effects of Porosity and Annealing on Catalyst Activity and Stability. Issue 16 (11th May 2020) - Ramesh, Rahul; Sawant, Sandesh Y.; Nandi, Dip K.; Kim, Tae Hyun; Kim, Deok Hyun; Han, Seung‐Min; Jang, Yujin; Ha, Myoung Gyu; Cho, Moo Hwan; Yoon, Taeho; Kim, Soo‐Hyun
Abstract: Molybdenum‐based compounds are considered as a potential replacement for expensive precious‐metal electrocatalysts for the hydrogen evolution reaction (HER) in acid electrolytes. However, coating of thin films of molybdenum nitride or carbide on a large‐area self‐standing substrate with high precision is still challenging. Here, MoN x is uniformly coated on carbon cloth (CC) and nitrogen‐doped carbon (NC)‐modified CC (NCCC) substrates by atomic layer deposition (ALD). The as‐deposited film has a nanocrystalline character close to amorphous and a composition of approximately Mo2 N with significant oxygen contamination, mainly at the surface. Among the as‐prepared ALD‐MoN x electrodes, the MoN x /NCCC has the highest HER activity (overpotential η ≈236 mV to achieve 10 mA cm −2 ) owing to the high surface area and porosity of the NCCC substrate. However, the durability of the electrode is poor, owing to the poor adhesion of NC powder on CC. Annealing MoN x /NCCC in H2 atmosphere at 400 °C improves both the activity and durability of the electrode without significant change in the phase or porosity. Annealing at an elevated temperature of 600 °C results in formation of a Mo2 C phase that further enhances the activity ( η ≈196 mV to achieve 10 mA cm −2 ), although there is a huge reduction in the porosity of the electrode as a consequence of the annealing. The structure of the electrode is also systematically investigated by electrochemical impedance spectroscopy (EIS). A deviation in the conventional Warburg impedance is observed in EIS of the NCCC‐based electrode and is ascribed to the change in the H + ion diffusion characteristics, owing to the geometry of the pores. The change in porous nature with annealing and the loss in porosity are reflected in the EIS of H + ion diffusion observed at high‐frequency. The current work establishes a better understanding of the importance of various parameters for a highly active HER electrode and will help the development of a commercial electrode for HER using the ALD technique. Abstract : Pores for thought : The phase of Mo‐based catalysts and the porosity of the carbon‐based substrate both influence hydrogen evolution activity. The porosity of the electrode is reflected in its electrochemical impedance spectroscopy (EIS) response. There is a deviation in the conventional Warburg characteristic in the EIS for a highly porous electrode, which is ascribed to the change in H + ion diffusion characteristics, owing to the geometry of the pores.